2016
DOI: 10.1038/icb.2016.92
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase PTPN22 has dual roles in promoting pathogen versus homeostatic‐driven CD8 T‐cell responses

Abstract: PTPN22 (protein tyrosine phosphatase non receptor 22) encodes a tyrosine phosphatase that functions as a key regulator of immune homeostasis. In particular, PTPN22 inhibits T-cell receptor signaling and selectively promotes type I interferon responses in myeloid cells. To date, there is little information on the CD8 T-cell-intrinsic role of PTPN22 in response to a viral pathogen. We unexpectedly found that PTPN22-deficient virus-specific CD8 T cells failed to accumulate in wild-type hosts after lymphocytic cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…By utilizing the TCR transgenic system specific for the LCMV immunodominant epitope GP 33–41 (P14) and adoptive transfer experiments, we previously showed that P14.PTPN22 −/− CD8 T cells fail to expand in PTPN22-sufficient hosts following infection with the acute viral strain of LCMV (Arm) due to T cell-intrinsic defects in IFNAR signaling (12). Here, we show that PTPN22 promotes CTL exhaustion in the LCMV Cl13 system via T cell-extrinsic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By utilizing the TCR transgenic system specific for the LCMV immunodominant epitope GP 33–41 (P14) and adoptive transfer experiments, we previously showed that P14.PTPN22 −/− CD8 T cells fail to expand in PTPN22-sufficient hosts following infection with the acute viral strain of LCMV (Arm) due to T cell-intrinsic defects in IFNAR signaling (12). Here, we show that PTPN22 promotes CTL exhaustion in the LCMV Cl13 system via T cell-extrinsic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies addressing the role of Ptpn22 in antiviral immunity either by studying PTPN22 −/− mice or cells from carriers of the autoimmune-associated variant showed a clear link between PTPN22 and effective responses to acute viral infection (9). In the setting of acute lymphocytic choriomeningitis virus Armstrong (LCMV Arm) infection, it has been shown that mice deficient for PTPN22 produce reduced number of LCMV-specific cytotoxic lymphocytes (CTLs) due to a weakened innate immune response and T cell-intrinsic defects in response to type I IFNs (1012). However, pathogen control is largely unaltered, suggesting that the role of PTPN22 in the setting of acute LCMV Arm infection is largely dispensable (11).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, PTPN22 was important for limiting naïve T‐cell responses to weak agonist ova‐peptide variants. Furthermore, several studies have determined that the extent of T‐cell proliferation and activation under lymphopenic conditions in vivo is regulated by PTPN22 . Interestingly, in effector CD8 + cytotoxic T‐cells, the absence of PTPN22 reduced the threshold for activation in response to very low affinity, self‐antigen .…”
Section: T‐cell Activation and Ptpn22mentioning
confidence: 99%
“…В генерации сигналов, передаваемых от полипеп-тидных цепей комплекса TCR-CD3 наиболее важ-но наличие в цитоплазматической части комплекса активационной последовательности ITAM, которая связана с ZAP-70, ключевым фактором в передаче сигнала от TCR при его связывании с лигандом [76,109,111,114]. Кроме CD45, другим ключевым регулятором каскада активации транскрипционных факторов, влияющих на функционирование иммунокомпетентных клеток, является PTPN22 -регулятор иммунного гомеостаза, который ингибирует передачу сигналов Т-клеточного рецептора и селективного промотирования интерфе-ронов типа I, после активации рецепторов влияет на активность ZAP-70 посредством Lck-киназы [29,49]. Следует также отметить, что Т-клеточный рецептор за счет связи с другими молекулами, корецепторами, может передавать как сильные, так и слабые сигна-лы, которые необходимы как для поддержания вы-живания клеток на периферии, так и для создания механизмов аутотолерантности [112].…”
Section: роль рецепторов и ферментов в патогенезе миастении грависunclassified